Embolization of a complex pulmonary arteriovenous fistula and coarctation treatment with covered stent at the same session - (:unkn) unknown (My University, 2015)
0

Erolu-Günay E, Yalçın Y, Çetiner N, Arpaözü MB, Çevik B, Akalın F. Embolization of a complex pulmonary arteriovenous fistula and coarctation treatment with covered stent at the same session. Turk J Pediatr 2015; 57: 413-417. Pulmonary arteriovenous fistula (PAVF) are rare malformations that may cause serious complications such as paradoxical embolism, stroke, pulmonary hemorrhage and hemoptysis. Accompanying cardiac malformations such as aortic coarctation were not reported previously. Here we present a case of complex PAVF associated with aortic coarctation. The patient was treated successfully by transcatheter embolization of PAVF with amplatzer vascular plug I and II and implantation of a covered CP stent for coarctation at the same session.
Keywords: Pediatri